2002
DOI: 10.1007/s001270200011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression in three Latin American samples

Abstract: The present study indicates that the high prevalence of depression in the mothers of young children is present in developing as well as industrialized countries and represents a major public health hazard. Future cross-cultural studies of maternal depression will require methodologies that are sensitive both to contextual factors in which depressive affect is expressed and individual histories that follow the course and etiology of depressive disorders as a chronic, recurrent illness in women during the childb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 39 publications
9
53
2
2
Order By: Relevance
“…Women in developing countries have high rates of stress and depressive symptoms, 86,87 often associated with poverty, lack of support, and negative life events. Children of depressed mothers are at risk for poor development, in part mediated through inconsistent and unresponsive parenting.…”
Section: Social Environmental and Infectious Risks Social Risksmentioning
confidence: 99%
“…Women in developing countries have high rates of stress and depressive symptoms, 86,87 often associated with poverty, lack of support, and negative life events. Children of depressed mothers are at risk for poor development, in part mediated through inconsistent and unresponsive parenting.…”
Section: Social Environmental and Infectious Risks Social Risksmentioning
confidence: 99%
“…Additional common predisposing factors according to bibliography are low income and financial difficulties [21,23,98,116,144], free marital status [24,70,93,109,134,140,144,145], prenatal mood disorders [21,90,93,105,108], unwanted or unplanned pregnancy [21][22][23][24]89], poor marital and intrafamilial relationships [21,23,26,56,84,86,89,146,147], premature birth and infant's health problems [21-23, 84, 141, 147], low self-esteem [21,26,108,148], poor conditions of living [21,93,149], unemployment [8,21,23,26,8688], stressful life events [8,21,25,…”
Section: Cultural Diversity Of Risk Factorsmentioning
confidence: 99%
“…82 In addition, the rates of postpartum depression may fluctuate according to native or immigrant status, since acculturation stress appears to be conducive to more prominent postpartum difficulties. 90 A study designed to investigate the prevalence of depressive symptoms in two Latin American countries, Costa Rica and Chile 93 , observed that, albeit with different socio-demographic measures, rates of depression were comparable in developing countries of Latin America as well. In Brazil, among women of low income, 43% presented with at least one depressive episode during the first six months after birth and the prevalence of depressive episodes in the third month was 12%.…”
Section: Postpartum Depression Screening Scale -Pdssmentioning
confidence: 99%